Exploring the structural changes in nitrogen-fixing microorganisms of rhizosheath during the growth of Stipagrostis pennata in the desert. Issue 4 (30th April 2021) - Tian, Yongzhi; Ma, Xiaolin; Li, Yuanting; Cheng, Cong; An, Dengdi; Ge, Fengwei
Abstract: Purpose: Rhizosheath is an adaptive feature for the survival of Stipagrostis pennata in desert systems. Although microorganisms play important ecological roles in promoting the nitrogen cycle of rhizosheath, the diversity and function of nitrogen-fixing microorganism communities have not been fully understood. Materials and methods: Therefore, the aim of the present study is to explore the nitrogen fixation ability of rhizosheaths and the changes in abundance of nitrogen-fixing microorganisms at different growth periods of S. pennata . We sequenced the nifH gene through sequencing to identify the structure and diversity of nitrogen-fixing microorganisms of S. pennata at different growth periods of rhizosheaths. Results: A total of 1256 operational taxonomic units (OTUs) were identified by nifH sequence and distributed in different growth periods. There were five OTUs distributed in each sample at the same time, and the abundance and diversity of microorganisms in fruit period were much higher than those in other periods. Mainly four phyla were involved, among which Proteobacteria was the most abundant in all groups. Conclusions: In general, the present study investigated the abundance and characteristics of nitrogen-fixing microorganisms of rhizosheaths in different growth periods of S. pennata . It also may elucidate and indicate that the structure of nitrogen-fixing microorganisms of rhizosheaths in different growth periods of S. pennata had changed.